Twenty First Century Skill Attainment Using Creative Learning Cycle Method with Learning Management System Media (A Case Study of Basic Programming Subject in 11th Grade Computer and Networking Study SMKN 1 Cimahi) - Asyifa Imanda Septiana (Journal of Software Engineering, Information and Communication Technology (SEICT), 2021)
Twenty first century skills is a set of skills that has to be mastered by students in order to win new era competitions where the competitions are started to open globally. Several researches have shown that Creative Learning Cycle method can help students to master the twenty first century skills and make learning process more meaningful. The purpose of this research is to identify the influence of Creative Learning Cycle learning steps to the students’ twenty first century skills. Another purpose of the research is to make a learning management system (LMS) that might enhance learning process done with Creative Learning method. Aside to manage the learning process, LMS can be used as twenty first century skills evaluation media in each step because it has been integrated with twenty first century learning parameters according to the analysis that has been done before. Even though in the end the LMS that has been built cannot accommodate all Creative Learning Cycle learning steps, LMS still get positive response from the teacher and students who use it